Del Mandubracius del De Bello Gallico de C. Julio César al Endriago del Amadís de Gaula (11 parte) - Suárez Pallasá, Aquilino (1995)
Fil: Suárez Pallasá, Aquilino. Pontificia Universidad Católica Argentina; Argentina